Inclusion of students with visual disabilities in Physical Education classes (Revista horizonte, 2022)
The present study, had as a main objective to know the perceptionsthat the students with visual disability give, about their integration in Physical Education classes. The used methodology was cualitative of phenomenological type, using as a technique. the interview in deep kind.Twelve students with visual disabilities participated, blind students and students with low vision level, from Elementary and High Schools, from state and ssubsidized private from Concepcion province, Chile. The results indicated that the students awarded a favorable perceptionsin favor of their teachers around inclusion, the curriculum scenario of the Physical Education class is situated in the first important places compared to the other subjects, though they admit that thay can`t participate from all the activities that the teacher carries out, due to the lack of curricular adaptations and adequate materials. At the same time, their parents value them for their contributions to health and in the inclusion of their children. It can be said that the students admitthat there exist a good disposition, from their closer classmates as well as their teachers, to help them, though there is a lack of preparation from the teachers, more commitment with inclusion from schools in the delivery of materail resources, as well as, sensitization processes to the educational community in general. It is concluded that the teaachers are not trained to work with blind students or thgose with low vision, which barries as a consequence, a parcial segregation en Physical Education classes, on the other hand they demand in initial teachersprogram, contents which approach those inclusion processes.